Strategi Sinematografi dalam Menentukan Visual Kreatif pada Film Dokumenter ”2000 Untuk Parkir“ - Sanditya Zufar Buwono; Iwan Koswara; Jimi Narotama Mahameruaji (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2026)
This study analyzes the cinematography strategies in determining creative visuals in the documentary film "2000 for Parking: The Phenomenon of Illegal Parking Attendants in Jatinangor," which documents the practice of illegal parking for Rp2,000-Rp5,000 in the Sumedang educational area as a social critique of the weak supervision of public spaces. Using a descriptive qualitative approach with frame-by-frame content analysis based on Joseph V. Mascelli's 5Cs theory and Bill Nichols' expository mode, the results demonstrate the dominance of eye-level angles (65%), low-key natural lighting (70%), handheld shaky camera (40%), and match cuts to build empathy, urgency, and a persuasive three-act narrative about the phenomenon of urban poverty. This visual strategy represents a power imbalance through low angles and rack focus, resulting in a 40% increase in audience awareness based on test screenings. Budget limitations are overcome through authentic improvisation that distinguishes the film from conventional Indonesian documentaries. The study concludes that cinematography is an effective visual storyteller for social advocacy, suggesting the integration of VR and AI-assisted techniques for future productions.